2012
DOI: 10.2164/jandrol.110.012500
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Pain Has a Negative Impact on Sexuality in Testis Cancer Survivors

Abstract: Testis cancer is a disease that directly affects a man's sense of masculinity and involves treatments compromising sexual function. The aim of this study was to investigate the prevalence of sexual dysfunction and the influence of chronic pain on sexuality in long-term testis cancer survivors. Thus, we examined 539 patients after they had one testis removed because of a testicular germ cell tumor. Having completed oncologic therapy, all patients received a detailed questionnaire asking about the occurrence and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
37
0
6

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(44 citation statements)
references
References 34 publications
1
37
0
6
Order By: Relevance
“…The long-term follow-up may have introduced a recall bias, although a previous study suggested differential recall bias of sexual dysfunction occurred primarily within the first 12 months post treatment[38], so differential recall bias between cases and controls in this study was unlikely. In addition, the sample size was limited when stratified by disease subtypes and treatment strategy.…”
Section: Resultsmentioning
confidence: 94%
“…The long-term follow-up may have introduced a recall bias, although a previous study suggested differential recall bias of sexual dysfunction occurred primarily within the first 12 months post treatment[38], so differential recall bias between cases and controls in this study was unlikely. In addition, the sample size was limited when stratified by disease subtypes and treatment strategy.…”
Section: Resultsmentioning
confidence: 94%
“…In patients with radical orchidectomy, sexual desire rate and erectile dysfunction rate are 34.5% and 31.5%, respectively. 13 Even artificial testosterone supplements are not satisfactory because native testosterone levels are regulated by the hypothalamus-pituitary-gonadal axis. Superabundant supplementation would cause unwanted complications, such as hyperlipidemia, atherosclerosis, and other cardiovascular diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Chronic pain following various injuries or as a sequela of illnesses or medical treatment for illnesses such as chronic pain among cancer patients, can all cause EjD and DE (92). In a study Lew-Starowicz and Gellert, 539 patients suffering from chronic pain were requested to answer questions on sexual and ejaculatory function: 34.5% of testicular cancer survivors complained of reduced sexual desire, and sexual activity was reduced in 41.6% of them.…”
Section: Medications and Chronic Medical Conditionsmentioning
confidence: 99%